THE IMPLEMENTATION OF COOPERATIVE LEARNING USING STAD TECHNIQUES IN IMPROVING LEARNING OUTCOMES TOWARD CULINARY STUDENTS - Anisa Zahwa Akbara; Faris Haikal Akbar (Universitas Terbuka, 2022)
The learning method is one of the elements of learning that determines how well a teacher delivers learning materials so that learning objectives are attained. Unattractive learning methods can affect student learning outcomes. Therefore, this study aimed to determine and analyze the application of the learning method, namely the Cooperative Learning (CL) with the Student Teams Achievement Division (STAD) technique to improve learning outcomes for the subject matter of Milk and Its Processed Products for students at Jakarta State Vocational Highschool 38. Research method of the study used a quasi-experimental method. The research sample were students of 1st grade of Culinary in Jakarta State Vocational Highschool 38 who were taking the subject of Foodstuffs Knowledge. The results showed that the class which was applied CL method with STAD technique had an average score of improvement (delta pre-test and post-test) of 7.80, while the class that was applied the conventional method was 4.35. It was concluded that there is an increase in student learning outcomes in the subject of Foodstuffs Knowledge, especially the subject matter of milk and its processed products with the application of Cooperative Learning (CL) Student Teams Achievement Division (STAD) technique which is significantly better than conventional methods.